Model Pembinaan Warga Gereja Dalam Kitab Markus - Andar G Pasaribu; Iis O Situmeang; Ersindi R Saragih; Agnita S Silaban (Jurnal Magistra, 2023)
The model for cultivating congregation members in the Book of Mark is a single wickedness that is an important part of expanding the Christian family. This article intends to review examples of church community formation that are provided in the Book of Mark. The approach in this point uses a qualitative approach plus discussion of Biblical literature and knowledge of the context. The results of the analysis show that the Book of Mark provides various lessons and examples regarding the formation of congregation members. This article provides practical guidance for every church leader and Christian religious educator in carrying out the development of congregation members.